Integrated Analysis of Long Non-coding RNAs (lncRNAs) and mRNAs Reveals the Regulatory Role of lncRNAs Associated With Salt Resistance in Camellia sinensis - Wan, Siqing; Zhang, Yongheng; Duan, Mengsha; Huang, Linli; Wang, Weidong; Xu, Qingshan; Yang, Yajun; Yu, Youben (Frontiers in Plant Science, 2020)
Tea plant (Camellia sinensis), an important economic crop, is seriously affected by various abiotic stresses, including salt stress, which severely diminishes its widespread planting. However, little is known about the roles of long noncoding RNAs (lncRNAs) in transcriptional regulation under salt stress. In this study, high-throughput sequencing of tea shoots under salt-stress and control conditions was performed. Through sequencing analysis, 16452 unique lncRNAs were identified, including 172 differentially expressed lncRNAs. The results of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses of their cis- and trans-target genes showed that these differentially expressed lncRNAs play important roles in many pathways under salt stress. The data from the gene-specific antisense oligodeoxynucleotide-mediated reduction in the lncRNA MSTRG.139242.1 and its predicted interacting gene, TEA027212.1 (Ca2+-ATPase 13), in tea leaves revealed that MSTRG.139242.1 may function in the response of tea plants to high salinity. In addition, 12 lncRNAs were predicted to be target mimics of 17 known mature miRNAs, such as miR156, that are related to the salt-stress response in C. sinensis. Our results provide new insights into lncRNAs as ubiquitous regulators in response to salt stress in tea plants.